2020
DOI: 10.18553/jmcp.2020.26.7.826
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical and Economic Outcomes Associated with Palbociclib for HR-Positive/HER2 Negative Metastatic Breast Cancer: A Commentary

Abstract: Breast cancer is the second leading cause of cancer-related death among American women. 1 Breast cancer is a heterogeneous disease composed of distinct molecular subtypes that include luminal A and B, human epidermal growth factor receptor 2 (HER2) type, and triple-negative/basal-like. 2 As of 2020, the average risk for a woman to develop breast cancer in her life is 13% in the United States, with an estimated 276,480 new cases of invasive breast cancer and 48,530 new cases of noninvasive breast cancer expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…While the recommended starting dose is 125mg, a more careful approach is given to more fragile patients and/or with relevant comorbidities. With respect to dose reduction, 43.24% of patients in our study had the initial dose reduced, in line with previous real-world studies (ranging from 31% to 50%), which could suggest that this is the prevalence of palbociclib dose reduction in real-life context in this indication [10,22,25,26].…”
Section: Discussionsupporting
confidence: 90%
“…While the recommended starting dose is 125mg, a more careful approach is given to more fragile patients and/or with relevant comorbidities. With respect to dose reduction, 43.24% of patients in our study had the initial dose reduced, in line with previous real-world studies (ranging from 31% to 50%), which could suggest that this is the prevalence of palbociclib dose reduction in real-life context in this indication [10,22,25,26].…”
Section: Discussionsupporting
confidence: 90%
“…Cost is often associated with decreased adherence/ persistence, 12,14,17,30 but despite the cost of CDK4&6i's, 31 most patients in this sample paid either very little or nothing due to a combination of insurance and co-payment assistance. Most participants knew very little about co-payment assistance as these details were handled by oncology support staff.…”
Section: Dovepressmentioning
confidence: 83%
“…38 Thus, medication management is highly important for patients on OAMs due to narrow therapeutic ranges and safety margins associated with these drugs. 37 Given of the cost-effectiveness of ribociclib within our WTP, demonstrating it was cost-effective 71.7% of the time.…”
Section: Limitationsmentioning
confidence: 90%
“…However, a study on real-world clinical and economic outcomes of palbociclib indicated growing evidence of suboptimal effectiveness of oral anticancer medications (OAMs) due to significant low patient adherence, adverse effect profiles, and sociodemographic factors. 37 Although the study evaluated palbociclib, these findings can be applied equally to other CKD4/6 inhibitors. Adherence issues due to toxicity or other factors can lead to lower survival rates, increased risk of recurrence, and higher health care costs.…”
Section: Limitationsmentioning
confidence: 99%